Angular Trapping of Spherical Janus Particles. Issue 12 (13th September 2020) - Gao, Xiaoqing; Wang, Yali; He, Xuehao; Xu, Mengjun; Zhu, Jintao; Hu, Xiaodong; Hu, Xiaotang; Li, Hongbin; Hu, Chunguang
Abstract: Developing angular trapping methods, which enable optical tweezers to rotate a micronsized bead, is of great importance for studies of biomacromolecules in a wide range of torque‐generation processes. Here a novel controlled angular trapping method based on model composite Janus particles is reported, which consist of two hemispheres made of polystyrene and poly(methyl methacrylate). Through computational and experimental studies, the feasibility to control the rotation of a Janus particle in a linearly polarized laser trap is demonstrated. The results show that the Janus particle aligned its two hemispheres interface parallel to the laser propagation direction and polarization direction. The rotational state of the particle can be directly visualized by using a camera. The rotation of the Janus particle in the laser trap can be fully controlled in real time by controlling the laser polarization direction. The newly developed angular trapping technique has the great advantage of easy implementation and real‐time controllability. Considering the easy chemical preparation of Janus particles and implementation of the angular trapping, this novel method has the potential of becoming a general angular trapping method. It is anticipated that this new method will significantly broaden the availability of angular trapping in the biophysics community. Abstract : A novel angular trapping method is presented. By adjusting the polarization direction, the polystyrene/poly(methyl methacrylate) composite Janus particle can achieve controllable rotation in linearly polarized laser trap. It results from a combination of optical intensity distribution, refractive index distribution, and the overlapping volume. This method opens a new way in many applications.